Pembelajaran Behavioristik Madrasah dalam Meningkatkan Motivasi Belajar dan Ibadah Siswa - Khoir, Nova Robithotul; Ikhwan, Afiful (Jurnal Pendidikan Nusantara, 2022)
Technological progress is one of the big challenges for education in filtering out bad effects, especially for students. As a person in charge of providing guidance, direction, and role models, teachers are required not to be left behind by today's students in mastering technology. More specifically, shaping student morals is the teacher's job that cannot be replaced by technology. This study uses a qualitative approach to the case study method, which collects data by means of observation, interviews, and documentation at MI Muhammadiyah 6 Nglegok with the analysis of the Miles and Huberman models. From this research it was found that the relevant behavioristic theory was applied in learning in madrasas. Behavioristic learning theory with the principle of stimulus and response using the reward board media "point system" can increase students' learning motivation and worship. With this theory, students are more enthusiastic in learning and practicing worship.